Climate variability and change in Southern Mali: learning from farmer perceptions and on-farm trials - Traoré, B.; Wijk, Mark T. van; Descheemaeker, Katrien K.; Corbeels, Marc; Rufino, Mariana C.; Giller, Kenneth E. (Cambridge University Press, 2015)
Agricultural production in the Sudano–Sahelian zone of west Africa is highly vulnerable to the impacts of climate variability and climate change. The present study aimed to understand farmers’ perceptions of climate variability and change and to evaluate adaptation options together with farmers, including tactical management of planting date in combination with the use of mineral fertilizer. Farmers perceived an increase in annual rainfall variability, an increase in the occurrence of dry spells during the rainy season, and an increase in temperature. Overall, this is in line with the observed meteorological data. Drought tolerant, short maturing crop varieties and appropriate planting dates were the commonly preferred adaptation strategies to deal with climate variability. On-farm trials confirmed that planting delays significantly reduce crop yields. The use of mineral fertilizer is often promoted, but risky for smallholders: although larger fertilizer applications increased the yield of maize (Zea mays) and millet (Pennisetum glaucum) significantly, a gross margin analysis indicated that it did not lead to more profit for all farmers. We conclude that integrating management of nutrients and planting time with improved farmer access to timely weather information, especially on the onset of the rains, is critical to enhancing adaptive capacity to increased climate variability and change.